Towards the Future Village: An Integrated Planning Framework for Tianmu Village, Lin’an, China - Ju, Cheng (International Journal of Natural Resources and Environmental Studies, 2026)
Rural revitalization in contemporary China has progressed through successive policy frameworks, from physical environmental improvement under the Beautiful Countryside campaign to the more systemic ambitions of the Future Village initiative, which seeks to reconstruct rural communities as economically viable, ecologically sustainable, and digitally empowered units within the broader metropolitan economy. This paper presents an integrated planning framework developed for Tianmu Village, a mountain rural settlement located in Tianmu Mountain Township, Lin’an District, Hangzhou, Zhejiang Province. Situated at the gateway to the West Tianmu Mountain UNESCO Man and Biosphere Reserve, the village possesses an exceptional convergence of ecological landscape assets, layered cultural heritage, and an established rural hospitality economy — conditions that create both significant development opportunity and heightened risk of asset erosion through uncoordinated growth. The planning framework responds through five coordinated strategic interventions: comprehensive environmental remediation, targeted infrastructure and service improvement, thematic connectivity across dispersed heritage and landscape assets, industrial integration centered on bamboo culture, and digital empowerment of governance and visitor experience systems. The framework argues that durable rural tourism competitiveness depends not on the accumulation of generic amenities but on the articulation of a coherent, place-specific cultural identity grounded in the intersection of Tianmu’s bamboo productive landscape, mountain ecological character, and multi-layered settlement heritage. The governance dimensions of the proposal — including a federated homestay quality management structure and a village-scale digital platform integrating smart tourism, agricultural monitoring, and community service delivery — are argued to be as critical to long-term success as the physical planning interventions themselves